Recovery of CaO from CaSO4 via CO reduction decomposition under different atmospheres. (1st January 2022) - Xia, Xiao; Zhang, Liqiang; Li, Zhanyao; Yuan, Xueliang; Ma, Chunyuan; Song, Zhanlong; Chen, Guifang
Abstract: CaSO4 reduction decomposition for CaO preparation provides a theoretical basis for the utilization of the industrial byproduct, gypsum. In this study, the effects of temperature (950 °C–1150 °C), CO2 /CO partial-pressure ratio (1–15), CO concentration (1%–5%), and O2 concentration (1%–7%) on the preparation of CaO from CaSO4 by CO reduction decomposition under different reaction atmospheres were investigated. The physical properties of CaO prepared by the decomposition of CaSO4 and CaCO3 were analyzed and compared. Finally, the reaction mechanism of the reduction decomposition of CaSO4 to CaO by CO was studied. The findings reveal that CaSO4 can be completely decomposed into CaO when the reaction temperature exceeds 1000 °C, CO% ≥ 2%, and P(CO2 )/P(CO) ≥ 8. Furthermore, the addition of an appropriate amount of O2 can improve the yield of CaO in the products. In an O2 –CO–N2 atmosphere, where O2 % = 7% and CO% = 16%, CaSO4 can be completely decomposed into CaO without the addition of CO2 . The physical properties of CaO prepared by the reduction and decomposition of CaSO4 are better than those prepared by the calcination of CaCO3 . An analysis of the reaction mechanism of the reduction decomposition of CaSO4 by CO reveals that CaSO4 generates CaO and CaS simultaneously. In addition, CaS can react with unreacted CaSO4 to form CaO. Furthermore, it can react with CO2 to produce CaO if an appropriate amount of CO2 is added to the reaction atmosphere. The secondary interactions of CaS with CaSO4 and CO2 can significantly improve the yield of CaO in the product. Highlights: CaSO4 can be decomposed into CaO when t ≥ 1000 °C, CO% ≥ 2%, P(CO2 )/P(CO) ≥ 8. Adding a proper amount of O2 and CO2 can improve the yield of CaO. CaSO4 can be completely decomposed into CaO at 7% O2 + 16% CO + 1050 °C. The porestructure of CaO prepared by CaSO4 is better than that prepared by CaCO3 .